Pengaruh Kekuatan Otot Tungkai, Koordinasi Dan Percaya Diri Terhadap Ketepatan Menembak Ke Gawang - Sandi, Sandy Suardi (Prodi PGSD FKIP Universitas Nahdlatul Ulama Al Ghazali, 2021)
This study aims to determine whether or not there is a direct and indirect influence between leg muscle strength, coordination, confidence in the accuracy of shooting at goal at the Ragunan Sports School football branch. The research method used in this research is the survey method with the test measurement technique, while the analysis technique uses the path path analysis which examines the relationship between the research variables and measures the direct and indirect effects between one variable and another. Based on the research findings, exogenous variables consist of leg muscle strength (X1), coordination (X2), and self-confidence (X3). The endogenous variable consists of shooting accuracy at goal (Y). Namely: a) There is a positive influence between leg muscle strength (X1) on shooting accuracy at goal (Y) at the Ragunan Sports School football branch; b) There is a positive influence between leg muscle strength (X1) on self-confidence (X3) in the football branch of the Ragunan Sports School; c) There is a positive influence between coordination (X2) on self-confidence (X3) in the football branch of the Ragunan Sports School; d) There is a positive influence between leg muscle strength (X1) on shooting accuracy at goal (Y) through self-confidence (X3) at the Ragunan Sports School football branch. There is a positive influence between coordination (X2) on the accuracy of shooting at goal (Y) through confidence in the football branch of the Ragunan Sports School.